2016
DOI: 10.1111/rda.12839
|View full text |Cite
|
Sign up to set email alerts
|

Viability and growth of feline preantral follicles in vitro cultured with insulin growth factor and epidermal growth factor supplemented medium

Abstract: ContentsIn vitro culture of ovarian preantral follicles has emerged as a reproductive technology aimed at obtaining large amount of oocytes for in vitro embryo production. The addition of growth factors (GF) in the in vitro culture of preantral follicles of different species has provided superior results of follicular development, antrum formation and proliferation of granulosa cells. However, there are only few reports regarding the use of these factors on feline preantral follicle in vitro culture. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that EGF promotes not only the maturation of oocytes but also their fertilization ability and embryo development and inhibits the apoptosis of oocytes during maturation and promotes the expansion of cumulus cells ( 19 , 20 ). Notably, the stimulative effect is related to the dose of EGF ( 21 ). Because the EGF signaling system of cumulus-oocyte complexes (COCs) matured in vitro is not perfect, it is difficult to simulate the physiological environment of follicles, resulting in poor development ability of oocytes in vitro and limiting the utilization efficiency of oocytes ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The major roles of growth factors include the regulation of apoptosis, cell differentiation and proliferation (Chang, Qiao, & Leung, 2016;Knight & Glister, 2006). Epidermal growth factor (EGF) contributes to maintain the viability of isolated follicles at different stage of development (primordial and preantral) after 6 or 14 days of culture (Alves et al, 2017;Fujihara, Comizzoli, Keefer, Wildt, & Songsasen, 2014). Cat oocytes exposed to EGF during IVM developed until late embryo stages at higher rates, further confirming the positive effect of this growth factor (Gómez, Pope, Davis, Harris, & Dresser, 2001;Merlo, Iacono, Zambelli, Prati, & Belluzzi, 2005).…”
Section: Chemical Factorsmentioning
confidence: 99%
“…Cat oocytes exposed to EGF during IVM developed until late embryo stages at higher rates, further confirming the positive effect of this growth factor (Gómez, Pope, Davis, Harris, & Dresser, ; Merlo, Iacono, Zambelli, Prati, & Belluzzi, ). Insulin‐like growth factor‐I (IGF‐I), alone or combined with EGF, is useful to promote both preantral follicle growth and oocyte nuclear maturation, as documented by several studies (Alves et al., ; Kitiyanant, Saikhun, & Pavasuthipaisit, ; Yıldırım, Vural, Küplülü, Özcan, & Polat, ).…”
Section: Introductionmentioning
confidence: 99%
“…Granulosa cells (GCs), as a component in follicular units, are critical for supporting ovarian function and determining follicular fate through the function of estrogens, growth factors, and cytokines [1]. These factors have been categorized as follicular survival factors, including estradiol estrogen receptor α/β [2], insulin-like growth factor 1 (IGF-1) [3], epidermal growth factor [4], and follicular atresia factors, such as FOXO3/ FOXO1 [5,6], inhibin [7], and TNF-associated receptors [8]. GCs are autocrine, paracrine, and endocrine units.…”
Section: Introductionmentioning
confidence: 99%